Deoxynivalenol contamination in cereal-based foodstuffs from Spain: Systematic review and meta-analysis approach for exposure assessment. (February 2022) - Narváez, Alfonso; Castaldo, Luigi; Izzo, Luana; Pallarés, Noelia; Rodríguez-Carrasco, Yelko; Ritieni, Alberto
Abstract: The presence of deoxynivalenol (DON) has been repeatedly detected in cereal-based products collected from Spanish markets over the last years. Hence, the aim of this study was to conduct a systematic review and meta-analysis of the concentration and prevalence of DON in cereals and cereal-based products from Spanish markets intended for human consumption, in order to integrate the available data. Then, an exposure assessment was performed based on national consumption data. Results revealed a strong impact of DON in breakfast cereals (pooled concentration = 105.34 ng/g; pooled prevalence = 58%) and bread and derived products (pooled concentration = 95.17 ng/g; pooled prevalence = 67%). Meta-regression showed a decrease in DON prevalence ( p -value = 0.761) and concentration ( p -value = 0.027) over the last 15 years. Exposure assessment outlined a high exposure to DON, especially in infants and children below 3 years old that showed a 175% and 119% of the tolerable daily intake (TDI). Bread and derived products were the main contributor to DON throughout age groups, with %TDI values ranging from 12% to 34%. Therefore, the here-presented results provide more evidence about the non-negligible impact of DON in Spain as result of cereal-based products consumption. Highlights: First meta-analysis of DON contamination in cereal products from Spain. Significant decrease of DON concentration in cereal products over time. Non-significant decrease of DON prevalence in cereal products over time. Bread and derived products were the main contributors to DON exposure. Exposure to DON in population below 3 years old exceeded the TDI.